Детермінанти розвитку інклюзивного ринку праці в Україні - Хомюк, Наталія Леонідівна; Шматковська, Тетяна Олександрівна; Дзямулич, Микола Іванович; Гаряга, Леся Олегівна (Волинський національний університет імені Лесі Українки, 2024)
У статті розглянуто сучасні детермінанти розвитку інклюзивного ринку праці в Україні, які визначаються комплексом специфічних факторів, які впливають на процес інтеграції осіб з соціально вразливих груп населення. Доведено, що однією з ключових складових інклюзивного ринку праці є соціально-економічні умови, які формують фундамент для розвитку інклюзивної економіки. Визначено, що ступінь розвиткуекономіки, рівень безробіття та доступність фінансових ресурсів безпосередньо впливають на формування інклюзивного ринку праці. Крім того важливу роль у формуванні інклюзивного середовища також відіграє правове регулювання, включаючи взаємодію національних органів державного управління з міжнародною організацією праці. Доведено, що нормативні акти,спрямовані на захист прав соціально вразливих осіб, створюють необхідні умови для їхньої активної участі в економічній діяльності на ринку праці.
The article examines the modern determinants of the development of the inclusive labor market in Ukraine, which are determined by a complex of specific factors that affect the process of integration of people from socially vulnerable population groups. It has been proven that one of the key components of the inclusive labor market are socio-economic conditions that form the foundation for the development of an inclusive economy. It was determined that the degree of economic development, the level of unemployment and the availability of financial resources directly affect the formation of an inclusive labor market. In addition, an important role in the formation of an inclusive environment is also played by legal regulation, including the interaction of national public administration bodies with the international labor organization. It has been proven that normative acts aimed at protecting the rights of socially vulnerablepersons create the necessary conditions for their active participation in economic activity on the labor market. It was determined that the development and improvement of such normative legal acts is a strategic task for ensuring the sustainable development of the inclusive labor market in Ukraine. Socio-cultural factors that determine society's attitude towards socially vulnerable persons and shape openness and tolerance in the working environment are considered. It was determined that an effective policyof differentiation and acceptance of diversity can contribute to the creation of a positive climate for inclusive employment, promoting the development of diverse talents and skills among employees in order to strengthen the relevance of their qualifications to the demands of employers. It has been proven that educational opportunities for persons with disabilities play a key role in their integration into the inclusive labor market. It was found that the system of providing high-quality education and professional training, as well as the implementation of special support programs in general,contribute to the growth of the competitiveness of this group of workers in the labor market. It was determined that organizational aspects, such as the creation of specialized employment centers, functional support of enterprises that implement inclusive practices, as well as the development of corporate responsibility, contribute to the effective solution of the problems of integration of socially vulnerable persons in the field of work. It is proved that all the mentioned determinants are closely interrelated and interact with each other, forming a complex system of factors that influence the development of the inclusive labor market in Ukraine.
Keywords: ринок праці; робоча сила; інклюзивний розвиток; сталий розвиток; мобільність робочої сили; labor market; inclusive development; sustainable developmen; labor mobility; 331.526